Experimental Setup of the Fast Current Controller for the Buenos Aires Heavy Ion Microbeam - Vega, Nahuel Agustín (2019)
Recently we used the heavy ion microprobe of the Buenos Aires TANDAR Laboratory for Single Event Effects (SEE) and Total Dose (TD) experiments in electronics devices and components, requiring very low beam currents. The facility includes a fast beam switch that allows the control of the ion beam current and a mobile Si PIN (p-type, intrinsic, n-type) diode that directly measures the number of ions hitting the device. The fast beam deflector was used to reduce the current by producing a pulsed beam or generating a quasi-continuous (Poisson-like distributed) beam with currents ranging from tens to hundreds of ions/s. As an application for this current control method we present a single event effect (SEE) pulses map generated by a 32S8+ beam at 75 MeV on two 0.5 µm technology CMOS digital output buffers where the device was formed by cascading four CMOS inverters with increasing sizes from input to output to drive large loads. Using the same concept of pulse width modulated deflection, we developed a novel gradient scanning method. This system allows to produce in a single irradiation a distribution with a cumulative damage with a difference of two orders of magnitude at constant gradient. To demonstrate the method, we irradiated a lithium niobate monocrystal with 32S8+ beam at 75 MeV energy and later analyzed the produced damage by the micro-Raman technique and an optical profilomete.